Old Testament/Hebrew Bible Textbooks: Which Ones Are Best? - Matthews, Victor H. 1950-; Moyer, James Carroll 1941- (1991)
In the fifth part of a series of in-depth book review articles, Old Testament/Hebrew Bible textbooks published since 1980 (with one exception) are reviewed for how they used archaeology to illuminate biblical studies.
Keywords: Rezension